Surgical clinics of North America : gastric surgery - Beck, William C.; Bolton, John S.;Carbonell, Alfredo M.;Carr, Aaron;Conway, W. Charles;Dada, Stephen;Donn, Natalie;Fuhrman, George M. ;Martin, Ronald F. (Philadelphia, Pennsylvania : Saunders, 2011)
A comprehensive review on gastric surgery. It covers such topics as: gastric acid and digestive physiology, emergency ulcer surgery, anti reflux and hiatal hernia Surgery, GIST surgery and adjuvant surgery, achalasia surgery, gastric adenocarcinoma surgery and adjuvant therapy, minimally invasive gastric surgery, and more.
Gastric acid and digestive physiology -- Gastric motility physiology and surgical intervention -- Emergency ulcer surgery -- Gastroesophageal reflux disease -- Achalasia -- Gastric adenocarcinoma surgery and adjuvant therapy -- Gastrointestinal stromal tumor surgery and adjuvant therapy -- Minimally invasive gastric surgery -- Postgastrectomy syndromes -- Miscellaneous disorders and their management in gastric surgery: volvulus, carcinoid, lymphoma, gastric varices, and gastric outlet obstruction
Includes bibliographical references and index.
Keywords: STOMACH SURGERY